Somatic variants in autosomal dominant genes are a rare cause of sporadic Alzheimer's disease. Issue 12 (13th August 2018) - Nicolas, Gaël; Acuña‐Hidalgo, Rocío; Keogh, Michael J.; Quenez, Olivier; Steehouwer, Marloes; Lelieveld, Stefan; Rousseau, Stéphane; Richard, Anne‐Claire; Oud, Manon S.; Marguet, Florent; Laquerrière, Annie; Morris, Chris M.; et al.
Abstract: Introduction: A minority of patients with sporadic early‐onset Alzheimer's disease (AD) exhibit de novo germ line mutations in the autosomal dominant genes such as APP PSEN1, or PSEN2 . We hypothesized that negatively screened patients may harbor somatic variants in these genes. Methods: We applied an ultrasensitive approach based on single‐molecule molecular inversion probes followed by deep next generation sequencing of 11 genes to 100 brain and 355 blood samples from 445 sporadic patients with AD (>80% exhibited an early onset, <66 years). Results: We identified and confirmed nine somatic variants (allele fractions: 0.2%–10.8%): two APP, five SORL1, one NCSTN, and one MARK4 variants by independent amplicon‐based deep sequencing. Discussion: Two of the SORL1 variant might have contributed to the disease, the two APP variants were interpreted as likely benign and the other variants remained of unknown significance. Somatic variants in the autosomal dominant AD genes may not be a common cause of sporadic AD, including early onset cases.